Accidental self administration of xylazine in a veterinary nurse. Issue 773 (March 1990) - Samanta, A.; Roffe, C.; Woods, K. L.
Abstract : A 19 year old male veterinary nurse accidentally injected himself with 200 mg of xylazine (a muscle relaxant and sedative used in veterinary practice). He subsequently became comatose, hypotensive, bradycardic and acidotic. He required intensive supportive therapy, and made a full recovery over the next few hours. Xylazine toxicity in humans is very rare, and the effects are discussed.